Talkshow Interaktif Jejak Alumni: Menjembatani Transisi Karier dan Self-Efficacy Mahasiswa Tingkat Akhir Jurusan Pendidikan Agama Islam - Muh. Asyam Samjas; Baso Ilyas (Al-DYAS, 2026)
Career direction confusion, transition anxiety, and limited real-life understanding of professional pathways remain problems faced by final-year students of the Islamic Religious Education (PAI) Study Program. This community service activity aims to strengthen students’ career readiness through an interactive talk show based on alumni trajectories as an experiential model that is relevant, inspiring, and close to participants’ needs. This activity used a participatory-educational approach through a two-way dialogue forum, presentation of alumni narratives, reflective discussion, initial career consultation sessions, and documentation of participants’ follow-up plans. The activity partners consisted of 37 final-year students who were entering the transition phase toward the world of work. The results of the activity showed an increase in participants’ cognitive and emotional engagement, as reflected in increasingly specific and applicable questions related to CPNS selection, strategies for dealing with students with difficult characteristics, and relationship management with students’ parents or guardians. In addition, there was a shift in participants’ mindset from a passive and anxious attitude to a more anticipatory, reflective, and planned approach to career preparation. The concrete impact of the activity was reflected in the preparation of independent career mind mapping and the formation of small study groups as spaces for strengthening sustainable career readiness. The conclusion of the activity affirms that an interactive talk show based on alumni trajectories plays an important role in bridging the career transition of PAI students through the strengthening of motivation, professional insight, and career planning. The implications of this activity provide practical contributions for study programs in developing career mentoring services that are participatory, contextual, and based on alumni experience.